Petroleum-hydrocarbons biodegradation by Pseudomonas strains isolated from hydrocarbon-contaminated soil. - Benchouk, Amina; Chibani, Abdelwahab (My University, 2017)
Many indigenous microorganisms in water and soil are capable of degrading hydrocarbon contaminants. In this study, two bacterial strains were isolated from a contaminated soil of a refinery of Arzew (Oran). The isolated strains were identified as Pseudomonas aeruginosa (P3) and Pseudomonas fluoresens (P4). The capability of these isolates to degrade petroleum was performed by measuring the optical density, colony forming unit counts (CFU/ml) and concentration of total petroleum hydrocarbons (TPH). Degradation of Isomerate by these isolates was analyzed by gas chromatography with flame ionization detector (FID). Results indicated that the isolates can use petroleum as carbon source. Isolates P3 has the highest capability of hydrocarbons degradation (80.86% of biodegradation).
Keywords: Biodegradation, contaminated soil, Petroleum, Isomerate, Pseudomonas sp.